Efeito in vitro do ácido úrico sobre a frutosamina e HbA1c e impacto de diferentes condições de armazenamento sobre a frutosamina sérica - Scolari, Rogério (2020)
Laboratory tests are influenced by factors, which can cause errors in the analyte dosage. Among the main ones are the interference of several substances, such as uric acid, and the inadequate storage of the samples. Considering that hyperuricemia is one of the findings related to diabetes mellitus, investigating the association between uric acid and biomarkers such as fructosamine and HbA1c is of great importance, since these tests are used to monitor blood glucose in these individuals. In addition, there are few references about the interference of uric acid on these biomarkers, as well as limited information about the stability of fructosamine in different storage conditions. Therefore, this study aimed to investigate in vitro effect of uric acid on fructosamine and HbA1c, in addition to assessing the impact of different storage conditions and consecutive freeze-thaw cycles on fructosamine. The interference of uric acid was evaluated in pools of serum or blood samples, after the addition of 3.0 mmol/L (50.4 mg/ dL) uric acid solution, obtaining a final concentration of 0.55 mmol/L (9.2 mg/dL). Fructosamine was measured by the colorimetric method based on the reduction of nitroblue tetrazolium, using the automated analyzer BS 380® (Mindray). HbA1c was measured using a chromatographic method, via the D10® analyzer (Bio-Rad). To investigate the stability of fructosamine, serum samples were stored at 4° C, -20° C and -80° C for up to 28 days, being analyzed on days 1, 7, 14, 21 and 28. The effect of thermal stress caused by the freezing and thawing of the samples was evaluated after the samples were stored at -20° C or -80° C. Each sample was subjected to three cycles that occurred in a single day, with the fructosamine determination performed after each cycle. The addition of uric acid promoted an 8.3% increase in fructosamine, while HbA1c did not change. In addition, the storage of samples at 4°C, -20° C and -80° C, for up to 4 weeks, had a significant impact on the fructosamine concentration (P < 0.001). Significant changes on fructosamine levels were also observed after successive freeze-thaw cycles of the samples at -20° C and -80° C (P < 0.01). Thus, high concentrations of uric acid caused an increase in the concentrations of fructosamine, which was not observed in HbA1c. In addition, storage of the serum at different temperatures and conditions significantly altered the concentrations of fructosamine.